Pengaruh Kemampuan Literasi Digital Marketing Dan Strategi E-commerce Advertising Terhadap Peningkatan Volume Penjualan Pada Umkm : (Study Kasus Usaha Jamu Tradisional Ibu Melydel) - Drajat Himawan; Nur Aisyah; Akbar NPD Wahana (CV. KAMPUS AKADEMIK PUBLISING, 2024)
As time goes by, the role of digital media has become very important in the business world, therefore business actors must have the ability and strategy to utilize digital media to increase their sales volume. This research aims to determine the influence of digital marketing literacy skills on sales volume, the influence of e-commerce advertising strategies on sales volume, as well as the influence of digital marketing literacy skills and e-commerce advertising strategies simultaneously on sales volume. The population in this study is all resellers and employees from Mrs. Melydel's Traditional Herbal Medicine business, Cikandang Village, Kersana District, Brebes Regency, totaling 70 people and the entire population in this study was used as a sample. Data collection methods were carried out by observation, interviews and distributing questionnaires to resellers and business employees. Mrs. Melydel's Traditional Herbal Medicine using the online method via (google form). The research variables used as the focus of the research are digital marketing literacy skills (X1), e-commerce advertising strategy (X2), sales volume (Y). The data analysis technique used is multiple regression analysis using SPSS. According to the results of research using SPSS, it starts with validity and reliability tests and continues with classic assumption tests such as normality tests, multicollinearity tests, heteroscedasticity tests, followed by hypothesis tests, namely partial statistical tests (t tests) and simultaneous significant tests (f tests). and the results of simultaneous hypothesis testing produce a significant value of 0.000 < 0.05 and a calculated f value of 32.256 > t table value of 3.984. So it can be said that there is a simultaneous influence on the variables of digital marketing literacy ability (X1), e-commerce advertising strategy (X2) on sales volume (Y).